Environmental selection and resource allocation determine spatial patterns in picophytoplankton cell size. (5th May 2013) - Clark, James R.; Lenton, Timothy M.; Williams, Hywel T. P.; Daines, Stuart J.
Abstract : Here we describe a new trait‐based model for cellular resource allocation that we use to investigate the relative importance of different drivers for small cell size in phytoplankton. Using the model, we show that increased investment in nonscalable structural components with decreasing cell size leads to a trade‐off between cell size, nutrient and light affinity, and growth rate. Within the most extreme nutrient‐limited, stratified environments, resource competition theory then predicts a trend toward larger minimum cell size with increasing depth. We demonstrate that this explains observed trends using a marine ecosystem model that represents selection and adaptation of a diverse community defined by traits for cell size and subcellular resource allocation. This framework for linking cellular physiology to environmental selection can be used to investigate the adaptive response of the marine microbial community to environmental conditions and the adaptive value of variations in cellular physiology.